A noncarcinoma mouse cell line is nonsusceptible to Newcastle disease virus established by spontaneous immortalization - Hanlue Li; Zijie Zhou; Chuanyu Chang; Weiwei Shi; Yuzhen Li; Qiaolin Wei; Fanxing Meng; Jianxia Tian; Qiqi Hao; Jinming Liu; Haijin Liu; Zengqi Yang; et al. (Scientific Reports)
Abstract Newcastle disease virus (NDV), as an avian pathogen, can infect a broad spectrum of cell lines in vitro. However, noncarcinoma cell lines possessing nonsusceptibility to NDV are rare. Here, we isolated primary mouse embryonic fibroblasts (MEFs), which are nonsusceptible to NDV. MEF-derived cells were generated by passaging the cells over fifty times to achieve spontaneous immortalization. Two of the resulting cell lines were named SLM-21 and MEF50. Karyotype analysis revealed that SLM-21 has a near-tetraploid karyotype and that MEF50 shows a near-tetraploid and near-hexaploid chimeric karyotype. NDV exerted a significant cytopathic effect on MEF50, and substantial viral replication was observed. In contrast, NDV did not have a significant effect on SLM-21, indicating that SLM-21 was a nonsusceptible cell line to NDV, while MEF50 was a susceptible cell line. The NDV authentic sialic acid (SA) receptors SA 2,3-Gal and SA 2,6-Gal were expressed in SLM-21. Transcriptomic analysis revealed that the non-susceptibility of SLM-21 may be related to its broadly activated antiviral pathways and fine-tuned regulation of the cell cycle and DNA damage. This study provides a basic cell platform for exploring viral susceptibility and pathogenesis as well as host–virus interactions during NDV infection.